Pengaruh Dana Pihak Ketiga (Dpk), Kas, Dan SertifikatBank Indonesia Syariah (Sbis) Terhadap PembiayaanMudharabah Dan Musyarakah Pada Perbankan SyariahDi Indonesia Periode 2010-2014SKRIPSI - Untari, Leni; , Ir. Maulidyah Hasmarini, MS; , Dr. Imron Rosyadi, M.Ag (2016)
This research aims to determine the effect of depositor funds ( DPK ) , Cash and Islamic Certificate of Bank Indonesia ( SBIS ) to the Mudarabah and Musyarakah financing on Islamic Banking of Indonesia period 2010-2014 . The data used in this research is secondary data in the form of monthly time series . Analysis model used in this research is multiple linear regression using analysis Partial Adjustment Model ( PAM ) regression. The results showed that ( 1 ) Depositor Fund ( DPK ) variable has a significant positive effect on Mudarabah and Musyarakah . ( 2 ) Cash and Islamic Certificate of Bank Indonesia ( SBIS ) variable has a significant negative effect on the Mudarabah and Musyarakah . ( 3 ) Depositor Fund ( DPK ) , Cash and Bank Islamic Certificate of Bank Indonesia ( SBIS ) jointly significant effect on Mudarabah and Musyarakah financing .